2005
DOI: 10.1111/j.1744-697x.2005.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐segregation of AFLP and RAPD markers to apospory in Guineagrass (Panicum maximum Jacq.)

Abstract: SynopsisA genetic linkage map of guinea grass ( Panicum maximum Jacq.) was generated with nine of the AFLP markers found to be associated with apospory. These aposporyassociated markers were assigned to a linkage group having previous association with microsporogenesis of the aposporous guineagrass cultivar 'Natsukaze'. An aposporous linkage group was constructed utilizing 38 AFLP markers. Embryo sac analysis revealed that sexual and apomictic embryo sacs occurred at a frequency of 1 : 1, indicating simple inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 29 publications
4
41
0
Order By: Relevance
“…Since apomixis also enables more rapid and efficient breeding, if a gene for apomixis were discovered, transgenic apomictic crops would hold considerable promise. Accordingly, many research groups, including our own, have worked to isolation of apomixis genes, both through molecular marker analysis (Ebina et al 2005) and through gene expression analysis in apomictic flowers (Yamada-Akiyama et al 2009). Guineagrass is one of the model plants for apomixis in tropical grasses.…”
Section: Guineagrasssmentioning
confidence: 99%
See 3 more Smart Citations
“…Since apomixis also enables more rapid and efficient breeding, if a gene for apomixis were discovered, transgenic apomictic crops would hold considerable promise. Accordingly, many research groups, including our own, have worked to isolation of apomixis genes, both through molecular marker analysis (Ebina et al 2005) and through gene expression analysis in apomictic flowers (Yamada-Akiyama et al 2009). Guineagrass is one of the model plants for apomixis in tropical grasses.…”
Section: Guineagrasssmentioning
confidence: 99%
“…as molecular breeding tools for genetic improvement of brachiariagrass must be useful. The breeding population in Thailand was analyzed using AFLP analysis for apomixis, as was done in guineagrass (Ebina et al 2005). First, seven obvious apomictic plants in the first 40 progeny (among 250 total progeny) were selected.…”
Section: Brachiariagrass (1) Recent Breeding Effortsmentioning
confidence: 99%
See 2 more Smart Citations
“…In guineagrass, many markers linked to the apomixis locus were obtained by bulked segregation analysis (Ebina et al, 2005). In such studies of grass species, it has been widely observed that recombination in the region near the apomixis locus was strongly suppressed (Ozias-Akins et al, 2003).…”
Section: Genomic Studies Of Apomixismentioning
confidence: 99%